Jeopardized mental health of children and adolescents in coronavirus disease 2019 pandemic - Bohyun Jin; Sohee Lee; Un Sun Chung (Clinical and Experimental Pediatrics, 2022)
The coronavirus disease 2019 (COVID-19) outbreak became a worldwide pandemic in 2020. Social distancing measures, such as self-quarantine, lockdowns, and school closures, which have proven efficacy in various pandemic situations, remain in use in Korea. These measures prevented viral transmission to some extent; however, adverse effects have also resulted. First, the negative effect of social isolation on mental health is evident. This influences the psychiatric milieu of parents and children directly and indirectly. The most stressful factor among Korean youth was the restriction of outdoor activities. Increasing parenting burden result in increased screen time among youth, and social isolation created depressive mood with symptoms similar to those of attention deficit hyperactivity disorder and anxiety. Second, symptoms of posttraumatic stress disorder (PTSD) and somatization are prevalent among children and adolescents. The sense of threatened health and life during the pandemic, one symptom of PTSD, is a strong risk factor for somatization. Finally, the increased pattern of child abuse in pandemic indicates increased levels of emotional/psychological abuse and nonmedical neglect. Social isolation makes people less aware of these events. Because pediatricians evaluate pediatric patients and their families, they should regularly assess emotional/stress factors, especially when somatization is prominent during the pandemic, and cautiously recommend that families seek advice from mental health professionals when warranted. Primary physicians must understand the characteristics and aspects of child abuse in the COVID-19 pandemic, make efforts to identify signs of child abuse, and deliver accurate information and preventive strategies for child abuse to caregivers, thereby functioning as a professional guardian. To promote the mental health of parents and children during the COVID-19 pandemic, more research and cooperation among health professionals, families, governments, and schools are needed in the future.